Eine neue Funktion für HIF: die Umstellung des Metabolismus im Zellzyklus - Dreute, Jan; Pfisterer, Maximilian; Schmitz, M. Lienhard; Justus Liebig University Giessen (My University, 2024)
The family of hypoxia-inducible transcription factors (HIF) is typically activated by low oxygen concentrations. We observed a transient increase of the HIF-1α protein levels during the G1 phase of the cell cycle, designated as G1-HIF. This cell cycle-regulated form of HIF ensures cell proliferation and survival under conditions of metabolic stress by increasing the levels of key metabolites during the cell cycle. The generation of G1-HIF depends on an AMPK-mediated signaling pathway.
Keywords: ddc:610